MANAJEMEN KELAS - Siti Samiha; Connie Connie (Manajer Pendididikan, 2019)
This research identified the class management at Junior High School Number 3 Empat Lawang district. The design of the research was used descriptive qualitative research. The subjective of this research was the students grade VIII of Junior High School Number 3 Pendopo Empat Lawang district. The technique of collecting the data, the researcher used observation, interview, and documentation to class managemen of the students grade VIII in Junior High School Number 3 Pendopo Empat Lawang district. The result of this research showed that the design of class management can to the learning process (KBM) in the class, it becaused with the right class management the result of the learning will be more maximal.